Using evolution as a guide to engineer kranz-type c4 photosynthesis - Slewinski, Thomas L. (Frontiers in Plant Science, 2013)
Kranz-type C4 photosynthesis has independently and rapidly evolved over sixty times to dramatically increase radiation use efficiency in both monocots and eudicots. Indeed, it is one of the most exceptional examples of convergent evolution in the history of life. The repeated and rapid evolution of Kranz-type C4 suggests that it may be a derivative of a conserved developmental pathway that is present in all angiosperms. Here, I argue that the Kranz-type C4 photosynthetic system is an extension of the endodermis/starch sheath, that is normally only found in the roots and stems, into photosynthetic structures such as leaves. Support for this hypothesis was recently provided by a study that showed that the same genetic pathway that gives rise to the endodermis in roots, the SCARECROW/SHORT-ROOT radial pattering system, also regulates the development of Kranz anatomy and C4 physiology in leaves. This new hypothesis for the evolution of Kranz-type C4 photosynthesis has opened new opportunities to explore the underlying genetic networks that regulate the development and physiology of C4 and provides new potential avenues for the engineering of the mechanism into C3 crops.